Interval-Valued Neutrosophic Framework for Improving the Decision-Making on the Quality Evaluation of English Classics Translation - Ying Du (Neutrosophic Sets and Systems)
English translations of literary classics are a subject of interest for many scholars and evaluators. However, the evaluation of the translations is a complex and multifaceted task, which necessitates a balance between linguistic accuracy, cultural fidelity, and readability. This makes traditional methods often fall short of catching the uncertainties, ambiguities, and subjective judgments. In an attempt to bridge these gaps between computational linguistics and translation studies, we introduce a mathematically grounded IVNS approach to evaluate the translation of English classics by flexible modeling of the ambiguities inherent in translation decisions. Then, we introduced an extended version of the MULTIMOORA method, called MULTIVNSMOORA, that can simultaneously account for multiple, often conflicting criteria to ensure well-adjusted decision-making about translation quality. Finally, we present a case study on Don Quixote to validate the practical applicability of the proposed IVNS approach, by which we offer a reproducible framework for assessing translations of other English literary works.